Digital marketing strategy and consumer engagement towards purchase intentions of MSMEs Yogyakarta fashion goods - Farahiyah Inarah Putri; Mohd. Tajuddin, Rosita; Mohammad Noh, Liza Marziana (International Journal of Accounting, Finance and Business, 2024)
In order to survive in this uncertain global situation or Volatility, Uncertainty, Complexity, and Ambiguity (VUCA) era, Micro Small Medium Entrepreneur (MSMEs) in Yogyakarta must increase their digital sales efforts to access a wider consumer base. The Covid-19 pandemic since 2020 has exemplified the VUCA era by drastically reducing tourism, leading to widespread cancellations by international and local tourists, thereby negatively impacting MSMEs and their economic stability. This study explored how the digital marketing mix influences consumer purchase intention, examining how consumer engagement mediates this relationship. This study was guided by digital marketing mix theory, consumer engagement theory and purchase intention by theory planned behaviour. This study examined data from 316 potential online buyers of local products from Yogyakarta, collected via Google Forms distributed online, utilizing the snowball sampling technique to obtain the sample. The findings suggested that digital marketing mix has a significant association with consumer purchase intention. Furthermore, consumer engagement significantly mediated the relationship between digital marketing mix and consumer purchase behavior. A study with this framework has not been previously conducted for local products from Yogyakarta, particularly in the fashion sector, which is a prominent industry in Yogyakarta. Therefore, this research represented new findings that will be highly beneficial for MSMEs in the region. The findings of this study contributed to MSMEs by encouraging the adoption of digital marketing mix to reach a broader consumer base. Additionally, this research has provided valuable input to the government in developing training programs for MSMEs, thereby enhancing their abilities to effectively utilize digital technology